2011
DOI: 10.1007/s10641-011-9961-5
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, spatial distribution, and diet of endangered Hovsgol grayling (Thymallus nigrescens)

Abstract: The Hovsgol grayling, endemic to Lake Hovsgol, Mongolia, is considered endangered, but published descriptions of the species abundance, distribution, or behavior do not exist. We used hydroacoustics, vertical and horizontal gillnetting, zooplankton sampling, and stomach content analysis to characterize abundance, distribution, prey availability, and diet of Hovsgol grayling. Pelagic Hovsgol grayling densities averaged 34.2±6.8 individuals·ha −1 (biomass of 4.4±0.9 kg·ha −1 ) and were concentrated along the wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…In late July and early August of 2011, 2012 and 2013, vertical and horizontal gill nets were set throughout the lake, following longterm sampling protocols established by Ahrenstorff et al (2012).…”
Section: Fish and Invertebrate Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…In late July and early August of 2011, 2012 and 2013, vertical and horizontal gill nets were set throughout the lake, following longterm sampling protocols established by Ahrenstorff et al (2012).…”
Section: Fish and Invertebrate Collectionmentioning
confidence: 99%
“…Though Lake Hovsgol is believed to have formed 2-5 million years ago , recent fossil diatom evidence has revealed that the lake's ecosystem collapsed during the last glacial period (Karabanov et al, 2004). All but Hovsgol grayling exclusively inhabit the littoral zone (Ahrenstorff et al, 2012) and exhibit some degree of diet overlap (Olson, 2014;Young et al, 2015). All but Hovsgol grayling exclusively inhabit the littoral zone (Ahrenstorff et al, 2012) and exhibit some degree of diet overlap (Olson, 2014;Young et al, 2015).…”
Section: Our Study Revealed the Presence Of Pelagic And Littoral Morpmentioning
confidence: 99%
See 2 more Smart Citations
“…Size‐based diet differences have also been observed in a closely related lake‐dwelling grayling (Hovsgol grayling Thymallus nigrescens ) higher in the Eg River watershed, which shift from a diet of zooplankton at smaller sizes to benthic invertebrates at larger sizes (Ahrenstorff et al. ).…”
Section: Discussionmentioning
confidence: 96%